PERSEPSI PEMBELAJARAN DARING MATERI SEPAK BOLA DI MASA PANDEMI COVID-19 PADA PESERTA DIDIK SMP LKIA - Wahyudi, Adong; Haetami, Mimi; Triansyah, Andika (Universitas Tanjungpura, 2024)
Adong Wahyudi Nim F1101161001, Perceptions of Online Learning on Football Materials During the Covid-19 Pandemic in Middle School (SMP) LKIA Pontianak Students. Main advisor Mimi Haetami, M.Pd and assistant advisor Andika Triansyah, M.Or Online learning implemented by the government during the Covid-19 period drew opinions from various parties. The descriptive analysis of this study examines the perceptions of online learning with soccer material during the Covid-19 pandemic in Pontianak LKIA Middle School students. This study used a survey form by distributing questionnaires via Google form to 25 grade 8 students with 4 indicators combined in 26 questions. From the results of the study, it was found that 44.46% answered